Social Determinants of Maternal Mortality Trends in Banyumas Regency: A Qualitative Study - Dewi, Marta Isyana; Ganap, Eugenius Phyowai; Hakimi, Mohammad; Hadijono, Raden Soeryo (Indonesian Journal of Obstetrics and Gynecology, 2025)
Background: Indonesia reduced maternal mortality from 390 per 100,000 live births in 1994 to 228 in 2007, but this rose again to 305 in 2015. In Banyumas Regency, maternal mortality declined from 2014 to 2020 but increased again from 2021 to 2023. Purpose: This study aims to identify social determinants affecting maternal mortality trends in Banyumas from 2014 to 2023. Methods: A qualitative study was conducted following the Standards for Reporting Qualitative Research (SRQR). Data collection involved in-depth interviews with 45 respondents—including health office staff, hospital informants, midwives, and health cadres—and a Focus Group Discussion. Interviews and discussions were guided by semi-structured protocols to explore participants’ views on maternal health issues. Results: Most respondents had over three years of experience and were aged 40–50. Key themes emerged: challenges in maternal and neonatal health services, referral refusal influenced by sociocultural factors, emergency training for health workers, collaboration and tiered referral systems, and hospital standardization. Discussion: The five key determinants influencing maternal mortality rate in Banyumas Regency were identified: human resource adequacy in maternal care, continuity of emergency training, accessibility of referral systems and collaborations, and hospital standardization. Healthcare personnel shortages, especially post-Covid-19, also combined with inadequate emergency training, may affect the healthcare quality. Sociocultural beliefs and poor referral coordination lead to treatment delays, particularly in rural areas. Inconsistencies in hospital standardization further exacerbate access inequities. While maternal mortality showed a declining trend from 2014 to 2023 (excluding pandemic years), systemic challenges remain. Strengthening referral systems, improving hospital standards, continuous training, and culturally sensitive public education are crucial. Conclusion: Social determinants influencing maternal mortality trends include the adequacy of human resources, ongoing emergency maternal and neonatal training, accessible and integrated referral systems, consistent hospital accreditation standards (PONEK), and sociocultural factors. Addressing these areas is essential to improving maternal health outcomes in Banyumas